Treatment patterns and impact of glucocorticoids on health outcomes in generalized myasthenia gravis: a retrospective observational study based on the Medical Data Vision database in Japan - Teranishi, Hirofumi; Tsuda, Koichi; Harada, Daisuke; Yachendra, Challa; Nguyen, Anthony; Sato, Mai; Takahashi, Masanori P.; Blein, Cécile (Frontiers in Neurology, 2025)
IntroductionGeneralized myasthenia gravis (gMG) is a rare, chronic, autoimmune disorder with a substantial disease burden. Oral glucocorticoids (GCs) are one of the common early-line treatments used globally, but there are growing concerns regarding risks associated with GC adverse effects, which can have serious medical consequences. In Japan, an important gMG treatment goal is minimal disease manifestation with a low target GC dose (≤5 mg/day) to minimize GC exposure. This study aimed to assess gMG treatment patterns in Japan, with a focus on GC exposure and incident comorbidities associated with long-term GC use.MethodsThis was a retrospective, observational database study of patient data from the Medical Data Vision (MDV) database (2008–2022) in Japan. Adults (aged ≥18 years) with ≥2 gMG diagnosis records were considered. First gMG diagnosis (ocular MG excluded) between 2018 and 2021 was considered the index date. All available follow-up was considered if the patient had ≥1 activity in the database annually after the index date.ResultsOf 9,687 patients with gMG (mean age: 65 years; 56% female; follow-up period: 3.2 years) included in the study, 3,696 (38.2%) were newly diagnosed (2018 onwards) and 5,991 (61.8%) were previously diagnosed (before 2018). Acetylcholinesterase inhibitor (AChEi) and GC monotherapy were the most common initial therapies after index, and most patients were treated with combinations of AChEi, GC, and/or nonsteroidal immunosuppressive therapies (NSISTs). The average daily GC dose was 8.5 mg/day (newly diagnosed: 10.6 mg/day; previously diagnosed: 7.5 mg/day). The target daily dose of 5 mg/day was exceeded by 70% of GC-treated patients, and 26% exceeded 10 mg/day (newly diagnosed: 35%; previously diagnosed: 21%). Compared to patients with no GC exposure, GC use was dose-dependently associated with osteoporosis, thrombosis, diabetes, and hyperlipidemia/hypercholesterolemia, even at GC doses ≤5 mg/day.ConclusionMost patients were treated with AChEi, GC, or NSIST monotherapy or combination therapies and received GCs exceeding 5 mg/day, which was associated with developing several GC-associated comorbidities in a dose-dependent manner. To achieve treatment goals, patients with gMG may benefit from additional treatment approaches to reduce GC usage.